Determinants of Hardiness among Representatives of Three Generations in Modern Russia - Вера А. Федотова (Rossijskij psihologičeskij žurnal., 2020)
Introduction. Generational differences have been scarcely investigated. The factors that help individuals to cope with stressful factors and increasing tension are worth consideration in the context of present-day reality. This study addresses the predictors of hardiness in different generations of Russians. Methods. A sample of respondents from various regions of the Russian Federation, aged from 18 to 75 years, took part in the empirical study of values, subjective economic well-being, and hardiness factors. The study used the following techniques: (a) the PVQ-R technique for measuring individual values, (b) the Test of Hardiness by D. A. Leont'ev, (c) the Subjective Economic Well-being technique by V. A. Khashchenko, and (d) the Meaning-in-Life Orientations test (MOL) by D. A. Leont'ev), the modified version of the Purpose-in-Life test (PIL). Results. Representatives of generation Y have a higher overall level of hardiness. The external locus of control influences hardiness in all the three examined generations. This influence is positive for generations X and Y, and negative for baby boomers. Economic anxiety has a negative impact on hardiness in representatives of generations X, Y, and baby boomers. The values of individualism – ‘independence: thinking’ and ‘achievement’ – influence hardiness in representatives of generations X and Y. Discussion. Increased dissatisfaction with financial situation, the inability to save money, and increased economic anxiety decrease the level of hardiness in Russians. The increase in financial well-being can contribute to an increase in hardiness across all the groups of respondents. Independence in the choice of actions, ambitious goals in life, the desire to be successful, and the need for feeling safe and secure increase the ability to withstand stress among representatives of generations X and Y.